On Reduction Principle in Stability Theory for Systems with Random Perturbations - Stanzhitskii, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
For stochastic systems, we obtain an analog of the reduction principle that enables one to reduce the analysis of the stability of a system with random perturbations to the analysis of the stability of a deterministic system.